Women in British imperial airspace, 1922-1937 - Millward, Liz, 1966- (McGill-Queen's University Press, 2008)
"The romance of flying the airways that developed above the British empire between the two world wars seduced young women with the promise of independence, glamour, and adventure." "Using a wealth of archival material, Liz Millward investigates the very idea of airspace. She maps the contours of five forms of civilian airspace - the private, the commercial, the imperial, the national, and the body of the pilot herself - as concrete places through which social differences such as gender, class, race, and sexuality were reproduced and challenged." "Women in British Imperial Airspace is a provocative exploration of the often difficult and rebellious struggle of women pilots as they attempted to produce, define, and gain access to the spaces created when popular and commercial flying took off"--Jacket.